Happyland A History of the "Dirty Thirties" in Saskatchewan, 1914-1937 - McManus, Curtis (The West, 2011)
"Dirty Thirties" is the sobriquet commonly applied to the agricultural crisis in the drylands of southern Saskatchewan in Canada that coincided with the Great Depression, and it is generally assumed that prior to this period healthier, normal conditions prevailed. In Happyland, Curtis McManus contends that the "Dirty Thirties" actually began much earlier and were connected only peripherally to the Depression itself. McManus has mined the rarely consulted records of Rural Municipalities in Saskatchewan, as well as government documents, ministerial correspondence, local community histories, newspapers, and publications of relevant government departments, to tell a story of a quarter-century of stubborn persistence but also of absurdity, despair, social dislocation, moral corrosion, and inconsistent and often inept government policy. Thanks to McManuss rare and welcome blend of sound scholarship and living breathing prose, it is a gripping and evocative story as well.